Experimental Study of Amorphous Photovoltaic Systems in Indoor Performance with Different Coolants - Dessy Ade Pratiwi; Andi Ibrahim Soumi; Gumilang Wicaksono; Nurmuntaha Agung Nugraha; Azizah Fatmawati; Rizki Nurilyas Ahmad; Wafiq Kurniawan; Cahyo Jawoto Anggoro (Engineering Proceedings)
The aim of this research is to investigate the performance of indoor amorphous photovoltaic systems with PVC water cooling and compare them with those using heatsink cooling. The amorphous approach used in this study involves water flowing through a PVC pipe and a heatsink cooler. The circular heatsink that was used has fins all around it. The water flow through the pipe is pumped from the reservoir to the PVC pipe. The study found that a PVC water flow-based active cooling system is the most effective at preserving thermal stability and improving the performance of amorphous PV modules under high light intensity circumstances, providing insights for future advancements.